Strained Mercy: The Quality of Medical Care in Delhi - Das, Jishnu; Hammer, Jeffrey S. (World Bank, Washington, D.C., 2013)
The quality of medical care is a potentially important determinant of health outcomes. Nevertheless, it remains an understudied area. The limited research that exists defines quality either on the basis of drug availability or facility characteristics, but little is known about how provider quality affects the provision of health care. The authors address this gap through a survey in Delhi with two related components. They evaluate "competence" (what providers know) through vignettes and practice (what providers do) through direct clinical observation. Overall quality as measured by the competence necessary to recognize and handle common and dangerous conditions is quite low, albeit with tremendous variation. While there is some correlation with simple observed characteristics, there is still an enormous amount of variation within such categories. Further, even when providers know what to do they often do not do it in practice. This appears to be true in both the public and private sectors though for very different, and systematic, reasons. In the public sector providers are more likely to commit errors of omission-they are less likely to exert effort compared with their private counterparts. In the private sector, providers are prone to errors of commission-they are more likely to behave according to the patient's expectations, resulting in the inappropriate use of medications, the overuse of antibiotics, and increased expenditures. This has important policy implications for our understanding of how market failures and failures of regulation in the health sector affect the poor.